Alteration of O-GlcNAcylation affects assembly and axonal transport of neurofilament via phosphorylation. (17th April 2019) - Peng, Peng; Wang, Jingjing; Ding, Nan; Zhou, Mei; Gu, Zhongya; Shi, Yao; Gong, Chengxin; Zhao, Gang; Deng, Yanqiu
Highlights: Accumulation of hyperphosphorylated NFs in neuron bodies induces the impaired axonal transport and neurotransmission in AD. Reduced O-GlcNAclation leads to abnormal assembly and axonal transport of NFs via increased phosphorylation. Increased O-GlcNAclation plays a neuroprotective role to treat AD. Abstract: Neurofilaments (NFs), the most abundant cytoskeletal components in the mature neuron, are hyperphosphorylated and accumulated in the neuronal cell body of AD brain, and the abnormalities of NFs appear to contribute to neurodegeneration. Although previous studies have showed that O- GlcNAcylation and phosphorylation of NFs regulate each other reciprocally, the NFs O- GlcNAcylation and its effects on assembly and axonal transport are poorly explored. Here, we focus on the role of dysregulation of O- GlcNAcylation on structure and function of neurofilaments by corresponding phosphorylation. In the study, we found that decreased O- GlcNAcylation by intracerebroventricular administration of Alloxan, 6-diazo-5-oxonorleucine (Don) and okadaic acid (OA) in the rats resulted in increased phosphorylation with assembly of lower and shorter NFs. In contrast, in the sample of NAG-thiazoline (NAG-Ae) causing increased O- GlcNAcylation, NFs showed elongated filaments fibers and higher proportion of assembly. Furthermore, alloxan treatment induced abnormal accumulation of NFs bodies and delayed time of Fluorescence Recovery After Photobleaching (FRAP) in SK-N-SH cells, but the NAG-Ae treatment speeded up the axonal transport. Our experiments suggest that increased O- GlcNAcylation plays a key role in protecting the structure and function of NFs including filament assembly and axonal transport via decreased phosphorylation. These results expanded the function of O- GlcNAcylation in AD pathogenesis.